"Gulliver’s Travels" e il conservatorismo sovversivo delle stampe satiriche ottocentesche - Ilaria Natali (Studi Irlandesi)
The visual quality of Jonathan Swift’s Gulliver’s Travels, together with its popular and folkloric ingredients, has greatly contributed to the novel’s immediate transmedial reception and was central to its success during the so-called “golden age” of visual satire in the British Isles. Starting with the end of the eighteenth century, caricaturists transformed Swift’s work into a symbol of society’s mechanisms and structures. Indeed, in its frequent nineteenth-century adaptations into graphic form, Gulliver’s Travels has been exploited to identify social or political identity and otherness, to express suspicion against any form of authority, and to undermine monologic perspectives on current political events.